2008
DOI: 10.1016/j.stem.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Responsiveness to Exogenous Signals Is Limited by Caspase-3

Abstract: Limited responsiveness to inflammatory cytokines is a feature of adult hematopoietic stem cells and contributes to the relative quiescence and durability of the stem cell population in vivo. Here we report that the executioner Caspase, Caspase-3, unexpectedly participates in that process. Mice deficient in Caspase-3 had increased numbers of immunophenotypic long-term repopulating stem cells in association with multiple functional changes, most prominently cell cycling. Though these changes were cell autonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
122
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 34 publications
(42 reference statements)
8
122
0
1
Order By: Relevance
“…90 Caspase-7 has an additional role in proper functioning of odontoblasts as caspase-7 knockout mice show reduced dental mineralization. 91 A role for caspase-3 in differentiation of embryonic stem cells (ESCs) and hematopoietic stem cells (HSCs) has also been reported, 92,93 with caspase-3 deficiency-impeding differentiation Haematopoietic stem cell Caspase-3 Maintenance of stem-cell quiescence and response to external stimuli 93 New functions for old molecules S Shalini et al of these stem cell populations. Caspase activity is also required for macrophage colony-stimulating factor (M-CSF)-mediated differentiation of human peripheral blood monocytes.…”
Section: Caspases In Cell-fate Determination and Differentiationmentioning
confidence: 99%
“…90 Caspase-7 has an additional role in proper functioning of odontoblasts as caspase-7 knockout mice show reduced dental mineralization. 91 A role for caspase-3 in differentiation of embryonic stem cells (ESCs) and hematopoietic stem cells (HSCs) has also been reported, 92,93 with caspase-3 deficiency-impeding differentiation Haematopoietic stem cell Caspase-3 Maintenance of stem-cell quiescence and response to external stimuli 93 New functions for old molecules S Shalini et al of these stem cell populations. Caspase activity is also required for macrophage colony-stimulating factor (M-CSF)-mediated differentiation of human peripheral blood monocytes.…”
Section: Caspases In Cell-fate Determination and Differentiationmentioning
confidence: 99%
“…However, restoration of active MST1 in caspase null myoblasts provides only a partial rescue of the differentiation defect, indicating that caspase activity must engage additional substrates to promote or sustain nondeath cell-fate outcomes (6). Other reports have shown that caspase 3 regulates differentiation indirectly by targeting and inactivating proteins that maintain stem-cell self-renewal/pluripotency (8,9). Although these later interactions contribute to the caspase effect, the targeting of these proteins does not explain the widespread alterations in gene expression and genomic reprogramming that typify differentiation.…”
mentioning
confidence: 99%
“…Sox2, on the other hand, is expressed by fetal and adult neural stem cells and is required for their selfrenewal (Graham et al 2003;Suh et al 2007). Caspase-3 deficiency increases adult HSC numbers (Janzen et al 2008) just as it promotes the maintenance of ES cells (Fujita et al 2008). The Zfx transcription factor provides a particularly interesting example because it is required for the self-renewal of adult (but not fetal) HSCs in addition to ES cells (Galan-Caridad et al 2007).…”
Section: Fetal Germ-line Stem Cellsmentioning
confidence: 99%